Method to improve the coupling efficiency of a hemispherically lensed asymmetric tapered-core fiber - SAMBANTHAN, K; RAHMAN, F (2005)
In this paper, we present a simple method based on chemical etching to improve e the Coupling efficiency between a laser diode and a hemispherically lensed asymmetric tapered-core fiber. An improvement of its high as 36.91% was observed from the method. We also present it theoretical model to determine the coupling efficiency, based on the ABCD transformation matrix method. In the analysis. we have taken into account the effect of spherical aberration of the lens and also the taper asymmetry. The theoretical model used in the analysis showed very close correlation between our theory and the experiment results. (c) 2005 Elsevier B.V. All rights reserved.